(untitled) (Docentes 2.0 Journal, 2023)
Mathematics is experiencing an increase in its usefulness and application, generating a "mathematization" in society. Consequently, new methods such as gamification, which includes game elements, are needed to achieve an innovative education system. The article’s objective was to analyze the state of the art on the advantages and implementation of gamification in mathematics. It is a strategy aimed at guaranteeing a better teaching-learning process for students in the Peruvian educational context. Study based on the analytical method. In its development, the content analysis methodology was applied based on the guidelines of the Prisma declaration on a sample of 20 studies published in different journals from the Scopus, PUBLINDEX, Scielo, and Latindex databases from 2018-2023. The results indicated a growing interest of teachers in the use of gamification as a learning strategy and a positive attitude on the part of students toward innovative experiences based on gamification. Among the benefits are the participation and involvement of students in the educational process, increased motivation, and the development of professional skills that improve their academic performance. In conclusion, it is necessary to consider this type of strategy to achieve the objectives proposed in the study plan.